CONSIGNMENT AND VENDOR MANAGED INVENTORY IN SINGLE-VENDOR MULTIPLE BUYERS SUPPLY CHAIN WITH FUZZY DEMAND - GANI, A. NAGOOR; DHARIK*, S. RAJA (International Journal of Mathematical Archive, 2018)
A policy for a single vendor with multiple buyers supply chain, as to be worked out based on a consignment (CS) and vendor managed inventory (VMI) policy. There are two types of partnerships between the vendor and buyers: independently acting vendor and buyers ii) the room to enter vendor managed inventory consignment partnership with the buyers by the vendor. Fuzzy mathematical model is also developed in which demand rate and production rate of the vendor are taken as trapezoidal fuzzy numbers. Modified graded mean integration representation method is used for defuzzifying the total cost. The benefits of the VMI&CS agreement can be studied by using (i) and (ii) relationship analytical and numerical results can also be provided. If the vendor has a capacity of flexibility, such an agreement will be more beneficial. Buyers find it more attractive while the significant order costs or the vendor’s setup cost is not large. By such a method, the vendor will find it convenient in making more frequent shipments with smaller costs.